Three dimensional CFD simulations of junction temperature of electronic components using nano-silver / Mazlan Mohamed and Rahim Atan - Mohamed, Mazlan; Atan, Rahim (Research Management Institute (RMI), 2011)
This paper presents the simulation of three dimensional numerical analyses of heat and fluid flow through chip package. 3D model of chip packages is built using GAMBIT and simulated using FLUENT software. The study was made for four chip packages arranged in line under different types of materials, inlet velocities and package (chip) powers. The results are presented in terms of average junction temperature and thermal resistance of each package The comparison between three types of material in terms of junction temperature has been observed and it was found that the junction temperature of the nano-silver had the lowest junction temperature as compared to epoxy and composite polymer. It also found that the nanosilver had the highest value of thermal conductivity as compared to the others. The strength of CFD software in handling heat transfer problems is proved to be excellent.